Superimposable outcomes for sequential and concomitant administration of adjuvant trastuzumab in HER2-positive breast cancer: Results from the SIGNAL/PHARE prospective cohort. (August 2017) - Pivot, Xavier; Fumoleau, Pierre; Pierga, Jean-Yves; Delaloge, Suzette; Bonnefoi, Hervé; Bachelot, Thomas; Jouannaud, Christelle; Bourgeois, Hugues; Rios, Maria; Soulié, Patrick; Jacquin, Jean-Philippe; Lavau-Denes, Sandrine; et al.
Abstract: Aim: Adjuvant clinical trials in early human epidermal growth factor receptor 2 (HER2)-positive breast cancer have assessed either sequential or concomitant incorporation of trastuzumab with chemotherapy; only the North Central Cancer Treatment Group (NCCTG)-N9831 trial prospectively compared both modalities. In routine trastuzumab has been incorporated into a concurrent regimen with taxane chemotherapy instead of sequential modality on the basis of a positive risk-benefit ratio. This present study assessed sequential versus concomitant administration of adjuvant trastuzumab. Methods: A population combining patients from Protocol for Herceptin ® as Adjuvant therapy with Reduced Exposure (PHARE) a randomised phase III clinical trial (NCT00381901) and SIGNAL (RECF1098) a prospective study specifically designed for Genome-wide Association Studies (GWAS) analyses was studied. In this cohort with 58 months of median follow-up, the comparison in the HER2-positive group of adjuvant trastuzumab and chemotherapy modalities was based on a propensity score methodology. Treatment modalities were based on physician's choice and comparisons adjustment were made by a propensity score methodology. Overall Survival (OS) and Disease-Free Survival (DFS) were estimated using the Kaplan–Meier method, and comparisons between groups were based on the log rank test. Results: The SIGNAL/PHARE cohort included 11, 728 breast cancer cases treated in adjuvant setting; some 5502 of them with HER2-positive tumour: 34.5% (1897/5502) were treated by sequential and 65.5% (3605/5502) by concomitant modality of administration for taxane-chemotherapy and trastuzumab. The adjusted comparison found similar OS (HR = 1.01; 95% CI: 0.86–1.19) and similar DFS (HR = 1.08; 95% CI: 0.96–1.21). Conclusion: These results suggest that the sequential administration of trastuzumab given after the completion of adjuvant chemotherapy might be as valid as the concomitant administration of trastuzumab and taxane chemotherapy in the adjuvant setting. Highlights: Trastuzumab is given concomitantly with taxane due to a positive risk-benefit in NCCTG-N9831. Propensity score methodology was used to compare adjuvant modalities in 11, 728 patients. Sequential adjuvant administration of trastuzumab might be as valid as the concomitant administration.